Allowing the A-Loud: Sonic Permission, Power, and Agency in the Classroom - Menard, Laura Jane; Friesen, Doug S. (Critical Studies in Improvisation / Études critiques en improvisation, 2026)
As part of an ongoing collaborative exploration, Menard and Friesen have been led to consider the conditions for sonic permissions in public classrooms: What is allowed and a-loud in educational space? Who—and what—determines which sounds are un/desirable? How do the decisions made by teachers in classroom spaces enable, or disable, students' sonic agency? It is these questions about sonic permissions and power that we explore in this paper. We examine how classroom sonic expectations as tacitly understood, and, through a methodology-in-the-making, invite our reader into a descriptive review process based on a recording of a high school classroom. Through reflection, we describe conditions required for sincere attempts at sonic egalitarianism both in our teaching and research practices, and invite other teacher-researcher-practitioners into the ‘productive stumbling’ of our line of inquiry and commitment-making.